Analisis Kesesuaian Syariah Pada Sistem Operasi Bisnis Multi Level Marketing (MLM) KK Indonesia dengan Fatwa DSN MUI NO: 75/DSN MUI/VII/2009 - Dwyanita, Ajeng; Zaki, Irham (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The rise of business Multi Level Marketing (MLM) which is growing rapidly in Indonesia made many people interest to join. However, it is still debated by scholars regarding the business operations of Multi Level Marketing (MLM). In addition, MUI has publish DSN MUI Fatwa Number: 75/DSN MUI/VII/2009 about Direct Selling Based On Islamic Law.This study aims to determine whether the business operations of the Multi Level Marketing (MLM) KK Indonesia is in conformity with the Shariah rules to follow 12 of the MUI fatwa or not .This study used a qualitative analysis using interview guide. The data used in this study is that the data derived from primary data obtained from fieldwork and secondary data derived from the literature and the MUI Fatwa DSN. In this study using data derived from the management of Multi Level Marketing (MLM) PT . KK Indonesian branch of Surabaya, East Java and Indonesian Ulema Council (MUI) East Java .The results of the study were operating Multi Level Marketing (MLM) KK Indonesias procedures are in line with the Indonesian Ulama Council fatwa DSN Number: 75/DSN MUI/VII/2009.